The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/gps.4286
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in the oldest old: an observational study and cluster analysis

Abstract: This is the first study to use the cluster analysis technique to identify meaningful subgroups among suicide victims in the oldest-old. The results reveal different patterns of suicide in the older population that may be relevant for clinical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“… 11 Sinyor et al identified three clusters among patients aged 80 and older who died by suicide: the first cluster included married or widowed patients, the second was composed of individuals who were living alone or socially isolated, and the third one included people suffering from dementia or depression. 12 …”
Section: Introductionmentioning
confidence: 99%
“… 11 Sinyor et al identified three clusters among patients aged 80 and older who died by suicide: the first cluster included married or widowed patients, the second was composed of individuals who were living alone or socially isolated, and the third one included people suffering from dementia or depression. 12 …”
Section: Introductionmentioning
confidence: 99%
“…That is not the case today. A cursory review of publications from the last year alone shows studies that have analysed coronial data to advance understanding of opioid deaths,19 intimate partner homicide,20 suicide among the elderly21 and deaths in nursing homes 22. We recently used coronial data to link the sharp decline suicide by motor vehicle exhaust asphyxiation with changes in emissions laws in Australia 23…”
Section: The Coroner's Public Health Rolementioning
confidence: 99%
“…The findings from the previous studies may be applied to doctors by helping them to make a treatment decision. A concept of clustering can be also used to find factors and group people who have a risk of suicide [4]. Clustering is a technique of grouping data containing similar characteristics.…”
Section: Introductionmentioning
confidence: 99%